Diagnostic value of serum cathepsin S in type 2 diabetic kidney disease - Ren, Xuejing; Wang, Wanqing; Cao, Huixia; Shao, Fengmin (Frontiers in Endocrinology, 2023)
Background: Identification of risk factors with causal effects on the incidence of diabetic kidney disease (DKD), together with early screening and intervention, are of great significance in delaying the progression of DKD to end-stage renal disease. Cathepsin S (Cat-S), a novel non-invasive diagnostic marker, mediates vascular endothelial dysfunction. The correlation between Cat-S and DKD has rarely been reported in clinical studies. Objective: To analyze whether Cat-S is a risk factor for DKD in type 2 diabetes mellitus (T2DM) and to evaluate the diagnostic value of serum Cat-S in DKD patients. Methods: Forty-three healthy subjects and 200 T2DM patients were enrolled. T2DM patients were divided into subgroups according to various criteria. Enzyme-linked immunosorbent assay was used to detect differences in serum Cat-S levels among different subgroups. Spearman correlation analysis was used to analyze correlations between serum Cat-S and clinical indicators. Multivariate logistic regression analysis was performed to explore risk factors for the occurrence of DKD and decreased renal function in T2DM patients. Results: Spearman analysis showed that serum Cat-S level was positively correlated with urine albumin creatinine ratio (r=0.76, P<0.05) and negatively correlated with estimated glomerular filtration rate (r=−0.54, P<0.01). Logistic regression analysis showed that increased serum Cat-S and cystatin C(CysC) levels were independent risk factors for early DKD and decreased renal function in T2DM patients (P<0.05). The area under the receiver operating characteristic curve for serum Cat-S was 0.900 for diagnosing DKD, the best cut-off value was 827.42 pg/mL, and the sensitivity and specificity were 71.6% and 98.8%, respectively. Thus, serum Cat-S was better than CysC for diagnosing DKD (for CysC, the area under the receiver operating characteristic curve was 0.791, the cut-off value was 1.16 mg/L, and the sensitivity and specificity of CysC were 47.4% and 98.8%, respectively). Conclusion: Increased serum Cat-S and CysC were independent risk factors for early DKD and decreased renal function in T2DM patients The diagnostic value of serum Cat-S was better than that of CysC in DKD. Monitoring of serum Cat-S levels could be helpful for early screening and assessment of the severity of DKD and could provide a new strategy for diagnosing DKD.